Enhancing recovery and reducing inflammation: the impact of enhanced recovery after surgery recommendations on inflammatory markers in laparoscopic surgery—a scoping review - Alves Bersot, Carlos Darcy; Ferreira Gomes Pereira, Lucas; Goncho, Victor Gabriel Vieira; Pereira, José Eduardo Guimarães; Falcão, Luiz Fernando dos Reis (Frontiers in Surgery, 2024)
IntroductionThe relationship between the Enhanced Recovery After Surgery (ERAS) guidelines and inflammatory markers in laparoscopic surgery has garnered increasing attention. These recommendations are designed to minimize surgical stress and potentially improve recovery outcomes by modifying perioperative care.ObjectiveThis scoping review aims to evaluate the impact of ERAS recommendations on inflammatory markers in patients undergoing laparoscopic surgeries, identifying current research gaps and consolidating findings from existing studies.MethodsGuided by the Cochrane Handbook for Systematic Reviews and adhering to the PRISMA-ScR guidelines, this review analyzed studies from databases like PubMed, Scopus, and Cochrane Library. We included both randomized controlled trials and observational studies that assessed inflammatory markers such as C-reactive protein (CRP), white blood cells (WBC), and Interleukin-6 (IL-6) in laparoscopic surgery patients managed with ERAS recommendations.ResultsOut of 64 initial studies, 7 met the inclusion criteria, involving a total of 2,047 patients. Most of the studies focused on laparoscopic colorectal surgeries. Commonly assessed markers were CRP and WBC. The findings consistently showed that ERAS guideline could mitigate the inflammatory response, evidenced by reduced levels of CRP and IL-6, which correlated with fewer postoperative complications and expedited recovery.ConclusionERAS recommendations appear to beneficially modulate inflammatory responses in laparoscopic surgery, which suggests a potential for enhanced recovery outcomes. However, the evidence is currently limited by the small number of studies and inherent methodological biases. Further robust RCTs are required to strengthen the evidence base and refine these protocols for broader clinical application. Systematic Review Registrationhttps://osf.io/tj8mw/